Pumpkin Seeds (Cucurbita moschata) as a Sustainable Anthelmintic and Nutritional Intervention for Helminthiasis: A Literature Synthesis - Alam, Syamsul (Unified Health Critical Research, 2025)
Helminthiasis remains a major public health issue in tropical and subtropical regions, particularly in low- and middle-income countries such as Indonesia. Soil-transmitted helminths (Ascaris lumbricoides, Trichuris trichiura, Necator americanus) contribute to malnutrition, anemia, stunting, and impaired cognitive development in children. While mass preventive drug administration (MPAD) with synthetic anthelmintics is effective, concerns about drug resistance highlight the need for alternative approaches. Pumpkin seeds (Cucurbita moschata), rich in cucurbitine and other nutrients, offer potential as a sustainable functional food with anthelmintic properties. This literature review (2013–2023) analyzed in vitro, in vivo, and clinical studies from multiple countries, showing significant reductions in worm counts and egg outputs across various species, including A. lumbricoides, T. trichiura, Hymenolepis nana, Haemonchus contortus, and Clonorchis sinensis. Cucurbitine exerts neuromuscular paralysis on worms, while compounds such as flavonoids, phytosterols, and zinc improve hematological and nutritional status. Optimal effects occurred at doses ≥300 mg/kg extract or 20 g/day powder, with praziquantel co-administration enhancing efficacy to 90%. C. moschata demonstrates dual benefits as a natural anthelmintic and nutritional intervention, supporting its integration into helminthiasis control strategies alongside MPAD, sanitation, and nutrition programs. Further large-scale trials are needed to confirm efficacy and establish standardized protocols.